Regulation of inflammation during wound healing: the function of mesenchymal stem cells and strategies for therapeutic enhancement - Gao, Mingnan; Guo, Han; Dong, Xuan; Wang, Zimao; Yang, Zheng; Shang, Qiaoli; Wang, Qiying (Frontiers in Pharmacology, 2024)
A wound takes a long time to heal and involves several steps. Following tissue injury, inflammation is the primary cause of tissue regeneration and repair processes. As a result, the pathophysiological processes involving skin damage, healing, and remodeling depend critically on the control of inflammation. The fact that it is a feasible target for improving the prognosis of wound healing has lately become clear. Mesenchymal stem cells (MSCs) are an innovative and effective therapeutic option for wound healing due to their immunomodulatory and paracrine properties. By controlling the inflammatory milieu of wounds through immunomodulation, transplanted MSCs have been shown to speed up the healing process. In addition to other immunomodulatory mechanisms, including handling neutrophil activity and modifying macrophage polarization, there may be modifications to the activation of T cells, natural killer (NK) cells, and dendritic cells (DCs). Furthermore, several studies have shown that pretreating MSCs improves their ability to modulate immunity. In this review, we summarize the existing knowledge about how MSCs influence local inflammation in wounds by influencing immunity to facilitate the healing process. We also provide an overview of MSCs optimizing techniques when used to treat wounds.